Effects of Dietary Isomaltooligosaccharide Levels on the Gut Microbiota, Immune Function of Sows, and the Diarrhea Rate of Their Offspring - Zhang, Longlin; Gu, Xueling; Wang, Jie; Liao, Shuang; Duan, Yehui; Li, Hao; Song, Zehe; He, Xi; Fan, Zhiyong (Frontiers in Microbiology, 2021)
To investigate the effects of dietary isomaltooligosaccharide (IMO) levels on the gut microbiota of sows and the diarrhea rate of their offspring, 120 multiparous gestating pig improvement company (PIC) sows with similar body conditions were selected and fed 1 of 6 diets: a basal diet with no supplement (control, CON), or a diet supplemented with 2.5 g/kg, 5.0 g/kg, 10.0 g/kg, 20.0 g/kg or 40.0 g/kg IMO (IMO1, IMO2, IMO3, IMO4 or IMO5 group, respectively). Results showed that dietary treatments did not affect the reproductive performance and colostrum composition of sows (P > 0.05). However, compared to the CON, IMO reduced the diarrhea rate of suckling piglets (P < 0.10) and improved the concentrations of colostrum IgA, IgG and IgM (P < 0.05). Moreover, IMO decreased concentrations of serum D-LA and LPS at farrowing and day 18 of lactation (L18) (P < 0.05). High-throughput pyrosequencing of the 16S rRNA demonstrated that IMO changed the composition of gut microbiota in different reproductive stages (day 107 of gestation, G107; day 10 of lactation, L10) (P < 0.05). At the genus level, the relative abundance of Parabacteroides and Slacki in G107 and Unclassified_Peptostreptococcaceae, Turicibacter, Sarcina and Coprococcus in L10 were increased in IMO groups but the YRC22 in G107 was decreased in IMO groups relative to the CON group (P < 0.05). Furthermore, the serum D-LA and LPS were negatively correlated with the genus Akkermansia and Parabacteroides but positively correlated with the genus YRC22 and Unclassified_Peptostreptococcaceae. Additionally, the colostrum IgA, IgG and IgM of sows were positively correlated with the genus Parabacteroides, Slackia and Coprococcus but negatively correlated with the genus YRC22. These findings indicated that IMO could promote the immune activation and improve the gut microbiota in sows during perinatal period, which may reduce the diarrhea rate of their offspring.